PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI FIRMA HUKUM - Martry Gilang Rosadi; Suharno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the influence of transformational leadership on the performance and discipline of law firm employees. Using a qualitative approach with exploratory descriptive methods, the study aims to uncover how transformational leadership practices influence the dynamics of performance and discipline within the context of human resource management in law firms. Through in-depth interviews, participant observation, and document analysis, the study explores the meaning of transformational leadership, employee responses, and its implications for the formation of a professional work culture. The results reveal a complex pattern in the relationship between transformational leadership and performance and discipline, mediated by the cultural context of the law firm organization.